BUKTI-BUKTI PERANAN JUNG NUSANTARA DIBANDING JUNG CINA DALAM PELAYARAN PADA AWAL MASEHI - Ida Bagus Putu Prajna Yogi (Balai Arkeologi Kalimantan Selatan, 2009)
In the early Anno Dominium, Chinese armadas were supported by high technology Jung to travel through the seas, to conquer and monopolize trade in the Southeast Asia. Chinese Jung also reached South Asia and Afrika either to sell or seek for goods. Nevertheless, there is no significant evidence to confirm that Chinese Jung were built and navigated by the Chinese. A number of archaeological finds and Chinese chronicles indicate that they used Jung originally came from Kunlun (Indonesian Archipelago). The journals also stated that Nusantara Jung had made voyages until Madagascar and were used by the Chinese and Persian for trade. This article discusses the contribute of Nusantara Jung in maritime voyaging in the ealy Anno Dominium